Evaluating Musculoskeletal Health and Ergonomics Awareness Among Bank Employees in Dhaka, Bangladesh - Musa, Abu Mohammad; Hossain, Md Shahadat; Islam, Md Samiul; Lira, Dilshad Noor; Shaikh, Abdul Kader; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Musculoskeletal disorder (MSD) is a significant occupational health concern, particularly in sedentary professions like banking. This study aimed to assess the prevalence and associated risk factors of Work-related Musculo Skeletal Disorders (WMSDs) among bank workers in Dhaka, Bangladesh. Data was collected with a standardized and pre-validated questionnaire from 300 bank employees of 35 branches of different public, private and international banks. The study revealed a high prevalence of WMSDs among bank workers, where significant risk factors are age, increased body mass index (BMI), longer working hours, extended job tenure, low knowledge of ergonomic training, poor awareness of good working posture, inadequate understanding of physiotherapy management for WMSDs, higher psychosocial stress, and increased activity levels. The study finally underscored several proactive measures. Ergonomic interventions are proposed as a preventive measure, emphasizing the importance of proper workstation design, posture, and regular exercise programs to mitigate the risk of WMSDs. Furthermore, the study advocates for the inclusion of occupational health physiotherapists within the banking sector to provide training, treatment, and rehabilitation, ultimately enhancing the well-being of bank workers and reducing the economic burden associated with WMSDs. It is necessary to implement comprehensive strategies to prevent WMSDs, emphasizing the importance of ergonomics, awareness, and specialized healthcare support in creating a healthier work environment for this vital sector of the economy. Dhaka Univ. J. Pharm. Sci. 23(2): 103-112, 2024 (December)